THE INVESTIGATION OF ENVIRONMENTAL SECURITY OF LADIES PARK USING CRIME PREVENTION THROUGH ENVIRONMENTAL DESIGN (CPTED) APPROACH - CASE STUDY- QOM NARGES PARK - Bazregari, Saman; Ostovareh, Mohadese (Ciência e Natura, 2016)
Environmental security enhancement (based on people understanding about their surroundings) is one of the most important approaches which are considered by advanced societies in the social sciences, management and “environment designing” in order to improve the use of “ladies parks”. Safety as an objective and subjective receiving is arising from the structure and layout of the environment. Therefore, to increase it, required criteria and standards should be considered for designing the ladies parks. The aim of this study is to investigate the environmental security of Ladies Park by using Crime Prevention through Environmental Design (CPTED) approach. This is a kind of descriptive and analytical study based on survey using inventory technique. This study expresses the problems of ladies parks by using CPTED approach. The statistical population of this research is Narges Park (Qom, Iran), the first park which has been constructed in the city for women. The results of the study show that women in their exclusive parks look for relaxation away from the masculine environment. The existence of environmental security and preventing people from seeing inside the park is one of the key factors which can increase the parks privacy and create peace of mind for users of the park. To increase the level of security in our environment, this study suggests the spaces proper design according to social cultural and ideological conditions of the city and park landscaping using Crime Prevention Through Environmental Design (CPTED) approach.